Intervención de la terapia respiratoria en el tratamiento de la sinusitis y la mejora de la calidad de vida. Niños 0 – 5 años, Hospital General Martin Icaza. Cantón Babahoyo mayo – septiembre 2019 - Cartagena Loor, Anggie Paulette (2019)
Sinusitis is the inflammation of the mucosa of the paranasal sinuses resulting from frequent colds, allergies, immunological problems, we know that it deteriorates the quality of life in children, to decrease the rate of cooling in the year. The objective of this research is to analyze the Intervention of Respiratory Therapy in the treatment of sinusitis and the improvement of the quality of life in children 0 - 5 years. An exhaustive analysis of respiratory therapy interventions in the treatment of sinusitis was carried out and we conclude that if we perform nasal lavage or secretion removal techniques in a timely manner, we will be able to keep the airways permeable and thus relieve the discomfort during the treatment of sinusitis and thus improve the quality of life of these children.